Microtubules mediate mitochondrial distribution in fission yeast. - Yaffe, M P (1996)
The Schizosaccharomyces pombe mutant, ban5-4, displays aberrant mitochondrial distribution. Incubation of this conditional-lethal mutant at the nonpermissive temperature led to aggregated mitochondria that were distributed asymmetrically within the cell. Development of this mitochondrial asymmetry but not mitochondrial aggregation required progression through the cell division cycle. Genetic analysis revealed that ban5-4 is an allele of atb2 encoding alpha 2-tubulin. Consistent with this finding, cells with the cold-sensitive nda3 mutation in beta-tubulin displayed aggregated and asymmetrically distributed mitochondria after incubation at lowered temperatures. These results indicate that microtubules mediate mitochondrial distribution in fission yeast and provide the first genetic evidence for the role of microtubules in mitochondrial movement.